Answer

Verified

450.6k+ views

Hint: First compare the equations with ${{a}_{1}}x+{{b}_{1}}y={{c}_{1}}$ and \[{{a}_{2}}x+{{b}_{2}}y={{c}_{2}}\] respectively and assign the values to them. After that use the condition \[\dfrac{{{a}_{1}}}{{{a}_{2}}}=\dfrac{{{b}_{1}}}{{{b}_{2}}}\ne \dfrac{{{c}_{1}}}{{{c}_{2}}}\] to find the value of ‘k’.

Complete step-by-step answer:

To find the value of ‘k’ we will first rewrite the system of equations as follows,

$\begin{align}

& 3x-4y+7=0 \\

& kx+3y-5=0 \\

\end{align}$

By shifting the constants on the left hand side of the equations given above we will get,

$3x-4y=-7$ ………………………………. (1)

$kx+3y=5$ ………………………………. (2)

If we compare the equation (1) with ${{a}_{1}}x+{{b}_{1}}y={{c}_{1}}$we will get,

${{a}_{1}}=3$, ${{b}_{1}}=-4$, ${{c}_{1}}=-7$………………………….. (3)

Also, if we compare the equation (2) with \[{{a}_{2}}x+{{b}_{2}}y={{c}_{2}}\] we will get,

\[{{a}_{2}}=k\], \[{{b}_{2}}=3\], \[{{c}_{2}}=5\] ………………………….. (4)

As given in the problem the system of equations has no solution and therefore to proceed further we should know the condition given below,

Concept:

The system of equations given by ${{a}_{1}}x+{{b}_{1}}y={{c}_{1}}$and\[{{a}_{2}}x+{{b}_{2}}y={{c}_{2}}\] has no solution if,

\[\dfrac{{{a}_{1}}}{{{a}_{2}}}=\dfrac{{{b}_{1}}}{{{b}_{2}}}\ne \dfrac{{{c}_{1}}}{{{c}_{2}}}\] ………………………………… (5)

i.e. we have to first check that whether \[\dfrac{{{b}_{1}}}{{{b}_{2}}}\ne \dfrac{{{c}_{1}}}{{{c}_{2}}}\] and then we should find the value of ‘k’ by using the equation \[\dfrac{{{a}_{1}}}{{{a}_{2}}}=\dfrac{{{b}_{1}}}{{{b}_{2}}}\].

To verify the above condition we will find all the terms separately,

Therefore we will first find \[\dfrac{{{a}_{1}}}{{{a}_{2}}}\] by using the equation (3) and equation (4) we will get,

\[\therefore \dfrac{{{a}_{1}}}{{{a}_{2}}}=\dfrac{3}{k}\] …………………………………………… (6)

Then we will find the value of \[\dfrac{{{b}_{1}}}{{{b}_{2}}}\] by using the equation (3) and equation (4) we will get,

\[\therefore \dfrac{{{b}_{1}}}{{{b}_{2}}}=\dfrac{-4}{3}\] …………………………………………… (7)

Lastly we will find the value of \[\dfrac{{{c}_{1}}}{{{c}_{2}}}\] by using the equation (3) and equation (4) we will get,

\[\therefore \dfrac{{{c}_{1}}}{{{c}_{2}}}=\dfrac{-7}{5}\] …………………………………………… (8)

Now, to check whether \[\dfrac{{{b}_{1}}}{{{b}_{2}}}\ne \dfrac{{{c}_{1}}}{{{c}_{2}}}\] first

Consider,

L.H.S. (Left Hand Side) \[=\dfrac{{{b}_{1}}}{{{b}_{2}}}=\dfrac{-4}{3}\] ……………….. (9)

R.H.S. (Right Hand Side) \[=\dfrac{{{c}_{1}}}{{{c}_{2}}}=\dfrac{-7}{5}\]……………… (10)

From equation (9) and equation (10) we can say that,

\[\dfrac{{{b}_{1}}}{{{b}_{2}}}\ne \dfrac{{{c}_{1}}}{{{c}_{2}}}\]

As the above condition is satisfied therefore to satisfy the condition given in problem \[\dfrac{{{a}_{1}}}{{{a}_{2}}}\] must be equal to\[\dfrac{{{b}_{1}}}{{{b}_{2}}}\].

Therefore it the system has no solution then,

\[\dfrac{{{a}_{1}}}{{{a}_{2}}}=\dfrac{{{b}_{1}}}{{{b}_{2}}}\]

If we out the value of equation (3) ad equation (4) we will get,

\[\therefore \dfrac{3}{k}=\dfrac{-4}{3}\]

By cross multiplication we can write the above equation as,

\[\therefore 3\times 3=-4\times k\]

\[\therefore 9=-4\times k\]

\[\therefore k=-\dfrac{9}{4}\]

Therefore if the system of equations has no solution then the value of ‘k’ should be equal to \[-\dfrac{9}{4}\]

Note: Don’t use Cramer’s rule in this problem as it will complicate the problem. After finding the value of ‘k’ please cross check your answer by substituting the value in \[\dfrac{3}{k}=\dfrac{-4}{3}\] for perfection.

Complete step-by-step answer:

To find the value of ‘k’ we will first rewrite the system of equations as follows,

$\begin{align}

& 3x-4y+7=0 \\

& kx+3y-5=0 \\

\end{align}$

By shifting the constants on the left hand side of the equations given above we will get,

$3x-4y=-7$ ………………………………. (1)

$kx+3y=5$ ………………………………. (2)

If we compare the equation (1) with ${{a}_{1}}x+{{b}_{1}}y={{c}_{1}}$we will get,

${{a}_{1}}=3$, ${{b}_{1}}=-4$, ${{c}_{1}}=-7$………………………….. (3)

Also, if we compare the equation (2) with \[{{a}_{2}}x+{{b}_{2}}y={{c}_{2}}\] we will get,

\[{{a}_{2}}=k\], \[{{b}_{2}}=3\], \[{{c}_{2}}=5\] ………………………….. (4)

As given in the problem the system of equations has no solution and therefore to proceed further we should know the condition given below,

Concept:

The system of equations given by ${{a}_{1}}x+{{b}_{1}}y={{c}_{1}}$and\[{{a}_{2}}x+{{b}_{2}}y={{c}_{2}}\] has no solution if,

\[\dfrac{{{a}_{1}}}{{{a}_{2}}}=\dfrac{{{b}_{1}}}{{{b}_{2}}}\ne \dfrac{{{c}_{1}}}{{{c}_{2}}}\] ………………………………… (5)

i.e. we have to first check that whether \[\dfrac{{{b}_{1}}}{{{b}_{2}}}\ne \dfrac{{{c}_{1}}}{{{c}_{2}}}\] and then we should find the value of ‘k’ by using the equation \[\dfrac{{{a}_{1}}}{{{a}_{2}}}=\dfrac{{{b}_{1}}}{{{b}_{2}}}\].

To verify the above condition we will find all the terms separately,

Therefore we will first find \[\dfrac{{{a}_{1}}}{{{a}_{2}}}\] by using the equation (3) and equation (4) we will get,

\[\therefore \dfrac{{{a}_{1}}}{{{a}_{2}}}=\dfrac{3}{k}\] …………………………………………… (6)

Then we will find the value of \[\dfrac{{{b}_{1}}}{{{b}_{2}}}\] by using the equation (3) and equation (4) we will get,

\[\therefore \dfrac{{{b}_{1}}}{{{b}_{2}}}=\dfrac{-4}{3}\] …………………………………………… (7)

Lastly we will find the value of \[\dfrac{{{c}_{1}}}{{{c}_{2}}}\] by using the equation (3) and equation (4) we will get,

\[\therefore \dfrac{{{c}_{1}}}{{{c}_{2}}}=\dfrac{-7}{5}\] …………………………………………… (8)

Now, to check whether \[\dfrac{{{b}_{1}}}{{{b}_{2}}}\ne \dfrac{{{c}_{1}}}{{{c}_{2}}}\] first

Consider,

L.H.S. (Left Hand Side) \[=\dfrac{{{b}_{1}}}{{{b}_{2}}}=\dfrac{-4}{3}\] ……………….. (9)

R.H.S. (Right Hand Side) \[=\dfrac{{{c}_{1}}}{{{c}_{2}}}=\dfrac{-7}{5}\]……………… (10)

From equation (9) and equation (10) we can say that,

\[\dfrac{{{b}_{1}}}{{{b}_{2}}}\ne \dfrac{{{c}_{1}}}{{{c}_{2}}}\]

As the above condition is satisfied therefore to satisfy the condition given in problem \[\dfrac{{{a}_{1}}}{{{a}_{2}}}\] must be equal to\[\dfrac{{{b}_{1}}}{{{b}_{2}}}\].

Therefore it the system has no solution then,

\[\dfrac{{{a}_{1}}}{{{a}_{2}}}=\dfrac{{{b}_{1}}}{{{b}_{2}}}\]

If we out the value of equation (3) ad equation (4) we will get,

\[\therefore \dfrac{3}{k}=\dfrac{-4}{3}\]

By cross multiplication we can write the above equation as,

\[\therefore 3\times 3=-4\times k\]

\[\therefore 9=-4\times k\]

\[\therefore k=-\dfrac{9}{4}\]

Therefore if the system of equations has no solution then the value of ‘k’ should be equal to \[-\dfrac{9}{4}\]

Note: Don’t use Cramer’s rule in this problem as it will complicate the problem. After finding the value of ‘k’ please cross check your answer by substituting the value in \[\dfrac{3}{k}=\dfrac{-4}{3}\] for perfection.

Recently Updated Pages

How many sigma and pi bonds are present in HCequiv class 11 chemistry CBSE

Why Are Noble Gases NonReactive class 11 chemistry CBSE

Let X and Y be the sets of all positive divisors of class 11 maths CBSE

Let x and y be 2 real numbers which satisfy the equations class 11 maths CBSE

Let x 4log 2sqrt 9k 1 + 7 and y dfrac132log 2sqrt5 class 11 maths CBSE

Let x22ax+b20 and x22bx+a20 be two equations Then the class 11 maths CBSE

Trending doubts

Which are the Top 10 Largest Countries of the World?

Fill the blanks with the suitable prepositions 1 The class 9 english CBSE

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

Give 10 examples for herbs , shrubs , climbers , creepers

Difference Between Plant Cell and Animal Cell

The Equation xxx + 2 is Satisfied when x is Equal to Class 10 Maths

Change the following sentences into negative and interrogative class 10 english CBSE

Differentiate between homogeneous and heterogeneous class 12 chemistry CBSE

Select the word that is correctly spelled a Twelveth class 10 english CBSE